Investigation of structural and dielectric properties of Gd3+ substituted nickel-zinc ferrite prepared via low-temperature citrate gel self-ignited process. (2022) - Sandeep, Yalagala; Rambabu, T.; Vinod, G.; Venkata Narayana, M.; Aravind, G.; Nathanial, V.
Abstract: The productive of nanocrystalline Gd 3+ substituted mixed Ni0.7 Zn0.3 Gdx Fe2-x O4 (where × = 0.000, 0.005, 0.010, 0.015, 0.020 and 0.025) spinel ferric material was synthesized using the low-temperature citrate assisted self-ignited process. The structure, microstructure, and elemental investigation were examined by XRD, SEM, EDX and TEM investigation. It revealed that the prepared accumulation a spinel system with an fd-3m space group. Scanning electron microscopy has shown the agglomeration of irregular morphology of nickel-zinc ferrite sample, EDX also confirms the presence of desired elements. TEM micrographs support the XRD data and the average particle size was estimated (approximately below 50 nm). The dielectric investigation is executed by using complex impedance spectroscopy in the frequencies 20 Hz to 2MH. Dielectric properties such as real ( ε ' ), imaginary ( ε ' ' ) parts in addition loss tangent (tan δ ) decreased by means of rising frequency for prepared ferric materials. The investigation of complex impedance outcomes showed "the capacitive and reactive characteristics". A study of the modulus electric evaluation suggested that relaxation processes in this nickel-zinc with Gd 3+ substituted compositions are of a "non-Debye's type". Replacing Fe ions through Gd3+ ions significantly impacts synthesised nano ferrites' electrical properties.